THE EFFECT OF LEVERAGE, CORPORATE GOVERNANCE, AND COMPANY CHARACTERISTICS ON TAX AVOIDANCE: Case Study On Manufacturing Companies Listed On The Jakarta Islamic Index For The Period 2019-2023 - Mayangsari, Dinita; Zuliansyah, A; Hanief Musthofa, Ujang (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
Indonesia uses a self-assessment tax collection system, namely a tax collection system that is enforced by means of taxpayers calculating, paying and reporting the amount of tax that has been adjusted to the laws and regulations independently. Unfortunately, this is actually an opportunity for taxpayers, in this case the agency, to take tax avoidance actions because of the freedom given by the tax law. The purpose of this study was to determine the effect of leverage, corporate governance as measured by institutional ownership, independent commissioners, audit committees, and company characteristics assessed by company size on tax avoidance in manufacturing companies listed on the Jakarta Islamic Index in 2019-2023. The sample was selected using purposive sampling method and collected 6 companies. This type of research is quantitative, with a causal associative approach. Using secondary data using Agency Theory and Trade off theory. The regression analysis model used is multiple linear regression with the help of SPSS 25. The results showed that partially leverage has a positive influence on tax avoidance. Corporate Governance (CG) with the proxy of the constitutional ownership board, independent commissioners and audit committee has no effect on tax avoidance. Leverage, Corporate Governance (CG) with proxies of constitutional ownership boards, independent commissioners and audit committees and company characteristics assessed from company size simultaneously have a significant effect on tax avoidance.